Gender Specificity of Structure of Aggression of Students - T V Nechepurenko (Peoples' Friendship University of Russia (RUDN University), 2008)
In the article the results of the gender research of the structure of aggression within the limits of the systemic-functional model suggested by Professor A.I. Krupnov are considered. The generality and specificity of the connections of variables in the structures of female and male aggression is shown.